Comparative Study between Nifedipine and Isoxsuprine in Suppression of Preterm Labour - حسن, لؤي; رمضان, لينا; خضورة, هزار (Latakia University Journal -Medical Sciences Series, 2020)
Background: Preterm labor is a cause of high rates of perinatal morbidity and mortality. The use of tocolytics is one of the efforts to handle the risk of preterm labor. Aim: The purpose of the study was to compare the efficacy of nifedipine against isoxsuprine in inhibiting preterm labour and also to evaluate maternal side effects and neonatal outcome. Materials and Methods: This randomized prospective study comprised of 92 patients with preterm labor with a gestational age between 24 – 36 weeks, admitted to Department of Obstetrics and Gynecology, Tishreen university Hospital, Lattakia, Syria, during the period of November 2018 to November 2019. The Patients who fullfield the inclusion criteria for the study were divided into 2 groups; the first consisted of 58 patients, treated with Nifedipine for tocolysis, the second consisted of 34 patients, who received isoxsuprine for tocolysis. Patients were monitored throughout the course of treatment and followed until delivery. Results: Baseline characteristics were well matched in both study groups. Mean prolongation of pregnancy was 31.6 days in Nifedipine and 22.9 days in Isoxsuprine group which was statistically significant. Success rate with Nifedipine was found to be 84.5% as compared to Isoxsuprine which was 70.5%. Maternal side effects like tachycardia (38.2%) and hypotension (14.7%) were common in Isoxsuprine group, while headache (51.7%) and facial flushing (56.9%) were common in Nifedipine group. The mean neonatal weight in Isoxsuprine group (2.07kg) was lower than Nifedipine group (2.38kg), with no differences in Apgar score between the two groups. The Cervical dilatation when applying the treatment had shown a significant relationship with the success of tocolysis in both drugs. Conclusion: Nifedipine is a better tolerated, more effective and safe tocolytic agent than Isoxsuprine with few maternal complications.